2009
DOI: 10.1073/pnas.0902087106
|View full text |Cite
|
Sign up to set email alerts
|

Protein-binding elements establish in the oocyte the primary imprint of the Prader-Willi/Angelman syndromes domain

Abstract: Imprinting of the PWS/AS 2.4 Mb domain in the human is controlled by a paternally active imprinting center (PWS-IC). PWS-IC on the maternal allele is methylated and inactivated by an 880-bp sequence (AS-IC) located 30 kb upstream. In this communication, we report the identification of 7 cis acting elements within AS-IC. The elements: DMR, DNS, 2 OCTA sequences, SOX, E1, and E2 bind specific proteins that form at least 2 protein complexes. Using variants of an imprinted transgene, mutated at the elements each a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“…Similarly, failure to establish the Snrpn ICR methylation imprint in Zfp57K/K eggs could be partially rescued by the paternally derived ZFP57 at post-implantation stages ). These observations, especially at the Snrpn ICR, are consistent with studies that report that methylation at the SNRPN ICR in humans might occur after fertilisation (El-Maarri et al 2001, Kaufman et al 2009note, however, that Geuns et al (2003) found that the human SNRPN ICR is methylated already in oocytes).…”
Section: Imprinting In the Absence Of Germline Dna Methylation Acquissupporting
confidence: 80%
“…Similarly, failure to establish the Snrpn ICR methylation imprint in Zfp57K/K eggs could be partially rescued by the paternally derived ZFP57 at post-implantation stages ). These observations, especially at the Snrpn ICR, are consistent with studies that report that methylation at the SNRPN ICR in humans might occur after fertilisation (El-Maarri et al 2001, Kaufman et al 2009note, however, that Geuns et al (2003) found that the human SNRPN ICR is methylated already in oocytes).…”
Section: Imprinting In the Absence Of Germline Dna Methylation Acquissupporting
confidence: 80%
“…A related situation may occur in the mouse Prader-Willi/Angelman region showing a complex imprinting control involving several cis-acting elements, one of which is not differentially methylated but is required to establish parental imprints at other sites (Kaufman et al 2009). Moreover, it was recently shown that in macaques, some ICRs that acquire a germline DNA methylation imprint in mice are not methylated in the germline and acquire a differential methylation mark only post-fertilization (A FergusonSmith, pers.…”
Section: Discussionmentioning
confidence: 99%
“…Das erhöhte Risiko konnte den Allen zweier Polymorphismen zugeordnet werden. Wahrscheinlich enthält das IC eine Bindungsstelle für einen trans-aktiven Faktor, der für die Etablierung des maternalen Imprints eine Rolle spielt und vermutlich mit unterschiedlicher Effizienz an die verschiedenen Allele bindet [21]. Darin könnte ein erhöhtes Risiko dafür liegen, dass das maternale Imprint nicht oder nicht vollstän-dig etabliert wird.…”
Section: Ursachenunclassified